18 Cases of pulmonary Mycobacterium abscessus: Clinical difference depending on the presence or absence of Mycobacterium avium complex. Issue 9 (September 2016) - Furuta, Kenjiro; Ito, Akihiro; Ishida, Tadashi; Ito, Yuhei; Sone, Naoyuki; Takaiwa, Takuya; Yokoyama, Toshihide; Tachibana, Hiromasa; Arita, Machiko; Hashimoto, Toru
Abstract: Background and objectives: It can be difficult to treat respiratory tract infections caused by Mycobacterium abscessus ( M. abscessus ) as there is no established treatment strategy. Complications involving other nontuberculous mycobacterial infections such as Mycobacterium avium complex (MAC) are also commonly observed. Methods: We investigated the clinical background and course of 18 cases of pulmonary M. abscessus infection treated over 8 years at Kurashiki Central Hospital. Radiological evaluation was performed using NICE scoring system, a method of semi-quantitative evaluation of imaging findings of pulmonary MAC infection. Results: The mean age of the 18 patients (males, 6; females, 12) was 74.7 years. The median follow-up period was 1316 days (95% confidence interval; 720–1675 days), and 11 patients were concomitantly infected with pulmonary MAC. Among the patients that underwent antibacterial treatment for M. abscessus, there was one MAC-complication case and one non-MAC-complication case. All MAC-complication cases underwent antibacterial treatment including clarithromycin. Chest X-ray NICE scores for all cases were 8.50 ± 5.45 and 10.94 ± 6.03 at baseline and follow-up, respectively ( p = 0.0063). For MAC-complication cases, scores were 8.36 ± 4.74 and 12.00 ± 6.02 at baseline and follow-up, respectively ( p = 0.00818), and for non-MAC-complication cases, scores were 8.71 ± 6.82 and 9.29 ± 6.13 at baseline and follow-up, respectively ( p = 0.356). MAC-complication cases were significantly further exacerbated than non-MAC-complication cases ( p = 0.027). Conclusions: Some cases of pulmonary M. abscessus infection progressed well without undergoing antibacterial treatment. In particular, results suggested that the clinical course of MAC-complication and non-MAC-complication cases differs.